Immobilisation of antibody on microporous silicon membranes - Herzog, G.; Raj, J.; Arrigan, Damien (Springer Wien, 2009)
The immobilisation of antibody on siliconmembranes containing arrays of micropores was studied.The membranes are modified by the deposition of aminopropyltriethoxysilane to functionalise the surface withamino groups. The surfaces are subsequently treated with1,4-phenyldiisothiocyanate and Cy5-labelled anti-HumanIgG. Fluorescence microscopy demonstrated the immobilisationof the labelled-antibody across the silicon surfacesbut not within the micropores. Electrochemistry at liquid/liquid interfaces located within the micropores demonstratedthat the pores remained open to ion transfer processes, asshown by the transfer of tetraethylammonium across themicro-interfaces between immiscible electrolyte solutions.These modified membranes will find applications inbioanalytical methods and sample preparation for theanalysis of complex biological samples.